Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1055/s-2002-33567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Endoscopic Retrograde Cholangiopancreatography Under Conscious Sedation and General Anesthesia

Abstract: The frequent use of general anesthesia for ERCP at our institution is related to the underlying diseases, which are frequently treated with complex and painful ERCP procedures. The efficacy of ERCP with general anesthesia supports a continued preference for general anesthesia rather than conscious sedation when complex and painful interventional ERCP procedures are planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 9 publications
(23 reference statements)
0
62
0
1
Order By: Relevance
“…During general anesthesia, there are issues with the need for muscle relaxants, prolonged extubation time, and instrumentation of the entire airway along with related disadvantages. Under deep sedation, however, problems with airway safety can occur, aspiration risk is increased, and cardiovascular complications can be involved (4).…”
Section: Endoscopic Retrograde Cholangiopancreatography (Ercp)mentioning
confidence: 99%
“…During general anesthesia, there are issues with the need for muscle relaxants, prolonged extubation time, and instrumentation of the entire airway along with related disadvantages. Under deep sedation, however, problems with airway safety can occur, aspiration risk is increased, and cardiovascular complications can be involved (4).…”
Section: Endoscopic Retrograde Cholangiopancreatography (Ercp)mentioning
confidence: 99%
“…General anesthesia is usually administered during ER CP after prior attempts using conscious sedation have failed [11,12] . A study by Raymondos et al [12] assessed the indications for carrying out ERCP examinations under general anesthesia or conscious sedation.…”
Section: Deciding On the Level Of Sedationmentioning
confidence: 99%
“…A study by Raymondos et al [12] assessed the indications for carrying out ERCP examinations under general anesthesia or conscious sedation. Patients with primary sclerosing cholangitis, liver transplants and those in whom painful dilations were planned received general anesthesia more frequently while conscious sedation was provided more frequently in patients with neoplasms and cholelithiasis.…”
Section: Deciding On the Level Of Sedationmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional study indicated that the procedural failure rate in patients undergoing ERCP with sedation was double the failure rate when general anesthesia was utilized (14 vs. 7 %). The higher failure rate with conscious sedation was entirely due to ERCPs that were terminated prematurely (8.5 %) due to inadequate sedation [6]. These data constitute powerful arguments for the use of deep propofol sedation or general anesthesia in patients undergoing ERCP and, indeed, this is the trend in many academic medical centers across the U.S.…”
mentioning
confidence: 98%